Mental Readiness of University Students in Facing the Industrial World Viewed from Scholarship Status in Palangkaraya City - Rafli Gustommy Pratama; Nadila Juni Yantiy; Arbayanti Arbayanti; Valerianus Gabun; Karyanti Karyanti; Asep Solikin; M. Fatchurrahman (Suluh: Jurnal Bimbingan dan Konseling, 2025)
Background: Mental readiness is a crucial aspect that determines students’ success in facing the transition from the academic world to the industrial workforce. Differences in social and economic backgrounds, including scholarship status, have the potential to influence students’ mental readiness in responding to the demands of the world of work. Aim: This study aims to analyze the level of students’ mental readiness in facing the industrial world based on scholarship status. Method: The research employed a quantitative approach with a descriptive-comparative design. The research subjects consisted of active university students grouped into scholarship recipients and non-scholarship recipients. Data were collected using a mental readiness questionnaire and analyzed using descriptive statistics in the form of frequencies and percentages. Result and Discussions: The results show that the majority of students fall into the high mental readiness category; however, non-scholarship students demonstrate a higher proportion of high mental readiness compared to scholarship recipients. Conversely, scholarship recipients show a relatively higher proportion of low mental readiness. These findings indicate differences in mental readiness based on scholarship status. Conclusion: The study concludes that scholarship status is associated with variations in students’ mental readiness to face the industrial world. Therefore, strengthening career guidance and counseling services is recommended to enhance students’ mental readiness, particularly for scholarship recipients.